2012
DOI: 10.1007/s12031-012-9759-8
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-21 Inhibitor Sensitizes Human Glioblastoma U251 Stem Cells to Chemotherapeutic Drug Temozolomide

Abstract: MicroRNAs (miRNAs) are small noncoding RNA molecules that regulate protein expression by cleaving or repressing the translation of target mRNAs. In mammals, their function mainly represses the target mRNA transcripts via imperfect complementary sequences in the 3'UTR of target mRNAs. Several miRNAs have been recently reported to be involved in modulation of glioma development, especially some upregulated miRNAs, such as microRNA-21 (miR-21), which has been found to function as an oncogene in cultured glioblast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 30 publications
3
35
0
1
Order By: Relevance
“…Shi et al 9 also showed that miR-125b functions in the development of GSC resistance to TMZ and that inhibiting miR-125b enhances GSC sensitivity to TMZ with respect to cell invasion. In addition, Zhang et al 10 found that neither miR-21 inhibitor nor TMZ induced GSC apoptosis but that miR-21 inhibitor combined with TMZ significantly enhanced apoptosis in GSCs.…”
Section: Retracted -Mir-423-5p Knockdown Enhances the Sensitivity Of mentioning
confidence: 99%
“…Shi et al 9 also showed that miR-125b functions in the development of GSC resistance to TMZ and that inhibiting miR-125b enhances GSC sensitivity to TMZ with respect to cell invasion. In addition, Zhang et al 10 found that neither miR-21 inhibitor nor TMZ induced GSC apoptosis but that miR-21 inhibitor combined with TMZ significantly enhanced apoptosis in GSCs.…”
Section: Retracted -Mir-423-5p Knockdown Enhances the Sensitivity Of mentioning
confidence: 99%
“…Mature functional miRNAs of B22 nucleotides are generated from long primary miRNA (pri-miRNA) transcripts and control gene expression at the post-transcriptional level by degrading or repressing target mRNAs [13]. Several miRNA mutations or deletions have proapoptotic or antiapoptotic effects in multiple human cancer stem cells, including GSCs [14]. Recent reports have shown that the overexpression or underexpression of miR-125b can have different effects on the invasion between human primary glioblastoma cells and corresponding stem cells [5], suggesting that miR-125b plays a more significant role during the differentiation process of glioblastoma stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Блокирование данной микро-РНК с помощью anti-miR-21 способствует образованию фосфорилированного гистона g-H2AX (индикатор двухцепочечных разрывов ДНК) и подавлению экспрессии phospho-Akt, активизации автофагии и апоптоза (в том числе путём ингибирования экспрессии Cdc25A) после облучения в клеточных линиях глиом [103,104]. MiR-21 также играет значительную роль в химиорезистентности клеток глиобластомы: применение ингибитора miR-21 совместно с темозоломидом усиливало апоптоз ОСК глиомы [105].…”
Section: микро-рнк как прогностические маркерыunclassified